Florida school shooting - Lüsted, Marcia Amidon (Special reports (Essential Library (Firm)), 2019)
Examines the events leading up to and following the Florida school shooting. Topics range from events of that day, the shooter, the aftermath, and the fight waged by the surviving teens to make change. Includes a glossary, resources for further information, and color photographs.